PENERAPAN BLOOKET SEBAGAI MEDIA PEMBELAJARAN DIGITAL TERHADAP HASIL BELAJAR MATEMATIKA KELAS 5 DI SDN KRATON 3 BANGKALAN - Qurrotu Aini; Cahyaningrum Cahyaningrum; Maulida Apriliska; Ika Rahmawati (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
This study emerged from the problem of low mathematics achievement, which is often linked to students’ limited participation and motivation during instruction. The study aimed to examine the effect of using the digital learning platform Blooket on competency attainment for the place value topic among fifth-grade students at SDN Kraton 3 Bangkalan. A quantitative approach was employed using a pre-experimental One-Group Pretest-Posttest design with 35 participants. Data were collected through interviews, observations, and pretests and posttests; analyses used descriptive statistics and a paired-samples t-test. Results showed the mean score increased from 69.14 to 79.14, with a significance value of 0.000 (p < 0.05). In conclusion, implementing Blooket as a digital learning medium had a positive impact on students’ mathematics learning outcomes for place value and also enhanced student participation and engagement during lessons.